(untitled) (Fiep Bulletin - online, 2013)
The present study had the objective a descriptive analysis of body fatness distribution in students of Rio de Janeiro. The sample studied was constituted of 213 students, being 122 of masculine gender (12.26 ± 1.48 years) an 91 of feminine gender (12.57 ± 1.29 years). The collects of data was made in state and private schools during Physical Education classes after parents authorization. The study was approved by Ethic Committee of Clementino Fraga Filho Hospital from the Federal University of Rio de Janeiro. The body composition was estimated by anthropometric method proposed by ISAK, measuring the skinfolds thickness, height ad total body mass. The statistic analysis was made in SPSS 13.0 for Windows. It was observed that for both genders, the regions of tight, abdominal and subsscapular, showed for all ages, higher values for skinfolds thickness than others body parts, being more expressive for females.